Audiovisual Learning Media with Package C Students' Interest in Learning - Afandi, Faris; Riyanto, Yatim; Susilo, Heryanto (Edukasi, 2024)
This research examines the relationship between the use of audiovisual learning media and the learning interest of Package C students at CLC Permata Bangsa Surabaya. Using the method in this research, namely quantitative correlational, involving 31 students, the results show a positive and significant relationship between two variables, data was collected through questionnaires and statistically analyzed. The results show a correlation coefficient of 0.568, greater than the table's critical value (DF = 29) of 0.355. The significance value of 0.001 (p < 0.05) supports the alternative hypothesis that audiovisual media has a relationship in increasing students' interest in learning, as well as helping the development of practical skills, especially in learning hydroponic topics. CLC Permata Bangsa plays an important role in the application of this technology in the learning process, which has a positive impact on improving the quality of education and developing students' skills. These findings emphasize the importance of audiovisual media in increasing the effectiveness of learning in non-formal education, especially in increasing students' interest in learning.